Gasification Reactor Design and Fabrication using mixture of Corn Cobs and Rice Husk as Fuel - FERDIAN SANUSI (NIM 13103055), ERY
Human dependence on unrenewable energy is increasing while it reserve is decreasing. One of the solutions for this problem is by taking the benefit from renewable energy of agricultural waste which agricultural country such as Indonesia has in a lot of amount. Agricultural waste that usually in the form of solids can be used in another prefered form by gasification process. In addition to producing gas that can be easily burned, this process is also environmental friendly compared to direct combustion. Another advantage is that its technology is quite simple so it will be able to be applied directly in the society. Willy Adriansyah has previously done biomass gasification research in PAU-ITB Thermodynamic Laboratory through the production of gasification reactor prototype using rice husk as fuel. The objective of this Final Project is to develop the prototype into a larger scale. In the meanwhile, corncob, another biomass fuel that has larger energy content, is mixed with the rice husk to increase the power output from the reactor. After the designing process, the gasification reactor is then fabricate and tested. The test was conducted for three kind of biomass fuel that was rice husk, corncobs and the mixture of both. The sample of the produced gases are taken to determine its compositions by using gas chromatography test. The chromatography test result shows that for different fuel used, the gas composition is differ. The conclusion can be taken by processing data from gasification reactor test result. It is concluded that the characteristics of gasification using mixture of corncob and rice husk was a combination of corncob gasification characteristics and rice husk gasification characteristics